Deficit policy within the framework of the stability and growth pact: Empirical results and lessons for the fiscal compact - Nicolas Afflatet (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2016)
This paper examines the question whether joining EMU or the breach of the Stability and Growth Pact in 2003 had an impact on the deficit policy of member states. The empirical analysis gives no hint for an alteration of deficit policy after having joined EMU or after having breached the Pact in 2003. These results can be explained with the fact that the Pact was undermined from its beginning and only had a limited disciplining effect henceforth. Otherwise the breakout of the ongoing debt crisis would not have been possible. These results advocate a sanctioning mechanism which cannot be influenced on a political level.
Keywords: E62; H62; 330; Stability and Growth Pact; Fiscal Rules; Deficits; Fiscal Policy